Development Prospects and Application Scenarios of Green Ammonia Energy Industry Under the Background of Carbon Peak and Neutrality - Zhibin LUO; Xiao SUN; Xiaotian GAO; Haizhou LIN; Guangtao ZHU (南方能源建设, 2023)
[Introduction] As a zero-carbon fuel, ammonia is easy to achieve safe and low-cost transportation and thus is considered to be an ideal energy source with the same development potential as hydrogen energy. Understanding the development status of core technologies in each link of the ammonia energy industry chain will help grasp the development prospects and direction of the ammonia energy industry. [Method] By investigating the core technologies and application scenarios involved in key links (including preparation, storage, transportation, and utilization) of the ammonia energy industry chain and analyzing the problems faced by the industry development, this study put forward corresponding development suggestions. [Result] Although the traditional Haber process for ammonia synthesis is very mature, the green transition of ammonia production can be achieved via green hydrogen feedstock substitution or adoption of new ammonia synthesis technologies such as photocatalysis, electrocatalysis, bioenzyme catalysis, and plasma drive. The storage and transportation of green ammonia can rely on the traditional synthetic ammonia infrastructure as well as supply chain, and the construction of supporting facilities such as ammonia fuel filling stations should be also strengthened. Ammonia combustion, ammonia fuel cells, ammonia energy storage and other ammonia energy utilization technologies need to be continously researched and developed as well as explored for application demonstration. [Conclusion] The development of green ammonia energy industry is in line with the requirements of building a clean, low-carbon, safe and efficient green energy system in China, and it has a positive impact on our country's energy security. However, the industrialization promotion of ammonia energy still faces many challenges and requires reasonable planning as well as layout and support from policy, finance, innovation platforms and standard system.